A Conjunctival Vascular Malformation as a Rare Presenting Sign of Wyburn–Mason Syndrome - Knoors, Louise; Buyse, Gunnar; Lagae, Lieven; Demaerel, Philippe; Kesteloot, Frank; Casteels, Ingele (Journal of Pediatric Neurology, 2018)
Wyburn–Mason syndrome is a rare condition that is characterized by ipsilateral arteriovenous malformations affecting the eye, brain, and facial skin. A conjunctival vascular dilation can be a rare ocular presenting sign. We report a 6-year-old boy who attended the hospital because of the sudden appearance of a conjunctival vascular lesion in his right eye. Inspection of his facial skin showed a subtle discoloration along the right trigeminal nerve and a vascular structure of the conjunctiva. Fundoscopy showed dilated and tortuous retinal vessels. Brain magnetic resonance imaging (MRI) revealed a large arteriovenous malformation involving the thalamus and perimesencephalic area. Ophthalmologic and neuroradiologic findings were consistent with the diagnosis of Wyburn–Mason syndrome. The sudden emergence of a vascular malformation in the conjunctiva should alert the clinician to perform an ophthalmoscopy, and in our patient, this finding was the clue to diagnosis of Wyburn–Mason syndrome. Because of the association between retinal and intracranial arteriovenous malformations, an MRI of the brain is strongly recommended in all patients with ocular arteriovenous malformations.
Keywords: Wyburn–Mason's syndrome; arteriovenous malformations; conjunctiva